Japanese Women's Speech through Life‐Transitions (1989‐2000): An Analysis of Youth Language Features. (20th May 2021) - Tanaka, Lidia; Okano, Kaori; Nakane, Ikuko; Maree, Claire; Iwasaki, Shimako; Takagi, Chie
Abstract : This study analyses four women's speech from Kobe who were interviewed by the same researcher in 1989 and in 2000. We focused on highly indexical pragmatic youth language features (discourse markers and end‐rising intonation) to understand about societal pressures that young women in Japan face when transitioning into adulthood. The analysis reveals a complex picture; some women use them more as time goes by, while others use them less. The vast ethnographic information helps us to understand their persona style (Eckert 2008), and to have an insight into their linguistic capital (Bourdieu and Boltanski 1978, Woolard 2008).